The Effect of Cooperative Learning Methods Picture and Picture to Reading Interests - Alpian, Yayan; Anggraeni, Sri Wulan; Nisa, Farhatun (International Conference on Elementary Education, 2020)
The problem of this research is the low reading interest of elementary school students. This study aims to determine the effectiveness of cooperative learning method of picture and picture type for reading interest of 4th grade students at SDN Margasari II, East Karawang District. This research is a type of quantitative research. The sample used in this study were 64 students in 4th grade students at SDN Margasari II. Data collection technique through the Reading Interest questionnaire. Data analysis technique to test the hypothesis is done by calculating the Independent-Smple T test. The results of hypothesis testing, there is an influence on the method of cooperative learning type picture and picture on the reading interest of 4th grade students. This significance was obtained by 0.025 because of the significance value of 0,025 < 0,05 or with a price of 2,292 ttable of 1,69 and n = 64 possible that Ho is rejected. From the results of this study it can be concluded that the cooperative learning method of picture and picture type affects the reading interest of 4th grade students